About farmers' bargaining power within the new CAP - Beatriz Velázquez; Bruno Buffaria (Agricultural and Food Economics, 2017)
This paper examines the current setting of instruments aimed at rebalancing unequal market power in the food chain. Particular attention is given to horizontal integration possibilities for farmers, and organisations of farmers, as derogations to competition policies contained in the Common Market Organisation Regulation (EU) 1308/2013 (CMO Regulation). Firstly, we propose a review of the literature that looks at the imperfect price transmission along the food chain. Secondly, we examine how CAP of instruments aimed at counterbalancing market inequalities along the chain have been functioning over time, notably if they contributed to improving efficiency, farmers' income and consumers' welfare. Thirdly, we assess the current setting of the CMO Regulation, in particular, the way derogations to the competition policy are defined (exclusions, e.g. producer's organisations). The main research question here is if the current setting does, or does not, allow attaining the objective of strengthening the bargaining power of producers, while at the same time avoiding the creation of monopoly power. Our research highlights that divergent results emerged from studies on the relation between size and profitability or efficiency, with evidence of significant economies of scale. Larger PO not only would be more profitable, but they also may offer more services to their members, especially when these services are associated with significant investment costs. In relation to policy measures aimed at improving the functioning of the food supply chain, the CMO Regulation relies on producer's organisations as the main vehicle for producer cooperation. But the new legislative setting could lead to the paradoxical consequence of impeding the functioning by challenging the existence and/or creation of POs.
Keywords: 330; Common Agricultural Policy; Competition Law; Producer's organisations